HIV diagnosis in Brazil: the impact of the COVID-19 pandemic - Marques, Nelson Pereira; Marques, Nádia Carolina Teixeira; Martelli, Daniella Reis Barbosa; Lucena, Edson Gomes de; Oliveira, Eduardo Araújo de; Martelli Júnior, Hercílio (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Letter to the editors